die sammlung toni gerber im kunstmuseum bern. - Kunstmuseum Bern (Bern : Kunstmuseum Bern, 1986)
Adamski, Hans Peter ;Brand, Heinz ; Bruhin, Anton ; Byars, James Lee ; Colombo, Gianni ; Dokoupil, Jiri Georg ; Eggenschwiler, Franz ; Engels, Pieter ; Fisher, Joel ; Fontana, Lucio ; Gachnang, Johannes ; Gertsch, Franz ; Hecht, David ; Höckelmann, Antonius ; Holstein, Peter ; Ikemura, Leiko ; Ingold, Res ; Jonas, Joan ; etc.
die sammlung toni gerber im Kunstmuseum Bern, 18. juni - 24. august 1986
boek